Ambivalensi Emosi Pengguna Instagram: Studi Kualitatif pada Pengguna Aktif dan Pasif - Agitia Kurniati Asrila; Silvi Juwita; Fauziah Taslim (Universitas Muhammadiyah Metro, 2026)
Instagram has become a prominent social media platform that shapes users’ emotional experiences through continuous online social interaction. Both active and passive users may encounter diverse emotional responses when viewing, posting, comparing, or engaging with content on the platform. This study aimed to explore the emotional experiences of Instagram users and analyze the dynamics of positive and negative emotions that emerge during platform use. A qualitative approach was employed using an open-ended questionnaire to capture users’ subjective emotional experiences. The study involved 136 Instagram users, consisting of 74 women and 62 men. The data were analyzed using thematic analysis to identify dominant emotional patterns and meanings associated with Instagram use. The findings revealed that the most frequently reported emotion was happiness (44%), followed by envy (24%), sadness (19%), anger (11%), fear (8%), and unidentified emotions (5%). The results further indicated that positive and negative emotions often appeared simultaneously, reflecting emotional ambivalence among Instagram users. This emotional ambivalence suggests that Instagram use does not produce a single emotional outcome but rather generates complex and overlapping affective experiences. Although negative emotions such as envy, sadness, anger, and fear were present, they did not necessarily indicate psychological crisis. Instead, these emotions functioned as daily stressors that users need to recognize and manage. This study highlights the psychological consequences of Instagram use and emphasizes the importance of emotional awareness, digital self-regulation, and reflective social media engagement. The findings provide implications for digital well-being programs, psychoeducation, and counseling interventions aimed at helping users manage emotional responses in social media environments.